Development of digital learning media with articulate storylines 3 based on students' algebraic thinking skills - Zulnaidi, Hutkemri; Sopiany, Hanifah Nurus; Hakim, Dori Lukman; Ardiyanti, Yusi; Yadav, Dharmendra Kumar; Sari, Rika Mulyati Mustika (International Journal of Didactic Mathematics in Distance Education, 2025)
This study aims to develop digital learning media designed to enhance students’ algebraic thinking skills, addressing the urgent need for innovative instructional tools that foster higher-order mathematical reasoning. The research was motivated by the persistently low levels of algebraic thinking among students and the lack of engaging media that can support the development of these essential skills. Employing a research and development (R&D) approach, the study utilized the ADDIE model—Analysis, Design, Development, Implementation, and Evaluation—to guide the creation of an Android-based learning application focused on systems of linear equations in two variables. The study involved media and content expert validators who assessed the quality, relevance, and usability of the developed media. Data were collected through questionnaires and guided interviews, and analyzed using descriptive qualitative methods. The final product is a digital application that integrates algebraic thinking tasks and interactive content to support student engagement and conceptual understanding. Validation results from both media and content experts confirmed that the digital learning media is pedagogically sound and suitable for classroom use. Furthermore, student feedback indicated that the application is user-friendly, visually engaging, contextually relevant, and effective in helping them practice and strengthen their algebraic thinking abilities. This research contributes to the growing field of educational technology by offering a validated digital tool specifically designed to target algebraic reasoning. Future research should explore the broader implementation of this media across diverse learning contexts and its long-term impact on students' mathematical performance and motivation.